The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1980
DOI: 10.1017/s0025315400041953
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in U.K. estuarine sediments and its availability to benthic organisms

Abstract: Arsenic concentrations in estuarine sediments from England and Wales range over three orders of magnitude. The highest concentrations, up to 2500 figjg, occur in the sediments of estuaries in south west England associated with past or present metalliferous mining activity. Strong correlations exist between arsenic and iron in 1 N-HC1 extracts of different estuarine sediments. The As/Fe ratio in those estuaries not contaminated with mine wastes is n x 10 ~4, increasing to 190 x 10 ~4 in metalliferous sediments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(47 citation statements)
references
References 21 publications
2
43
1
1
Order By: Relevance
“…Any single change in metal concentration may reflect either one or the simultaneous influence of both variables. The effect of weight-driven changes on trace metal concentrations can be significant (Phillips 1976, Simpson 1979, this paper) and if not accounted for, can seriously compromise results from organisms used as bioindicators to monitor contamination (Goldberg et al 1978) or to study metal bioavailability (Whitfield & Lewis 1976, Langston 1980, 1982, Luoma & Bryan 1982.…”
Section: Discussionmentioning
confidence: 99%
“…Any single change in metal concentration may reflect either one or the simultaneous influence of both variables. The effect of weight-driven changes on trace metal concentrations can be significant (Phillips 1976, Simpson 1979, this paper) and if not accounted for, can seriously compromise results from organisms used as bioindicators to monitor contamination (Goldberg et al 1978) or to study metal bioavailability (Whitfield & Lewis 1976, Langston 1980, 1982, Luoma & Bryan 1982.…”
Section: Discussionmentioning
confidence: 99%
“…Trace metals that are associated with the EP, CP, ERP, MRP, and OSP (Agemain and Chau 1976) have been demonstrated to be strongly correlated to the concentration of trace metals in various aquatic organisms after normalizing with naturally occurring sediment associated geochemical components (Louma and Bryan 1978;Langston 1980Langston , 1982Tessier et al 1984;Bourgoin et al 1991). Trace metals concentrations in the sediment non-residual fraction from all stations are illustrated in Figure 3.…”
Section: N O N -R E S I D U a L Trace M E T A L Concentrationsmentioning
confidence: 98%
“…Bivalves are generally assumed to be reliable bio-indicators to provide a time-integrated measure of aquatic contaminants (e.g., trace metals) bioavailability (Phillips and Segar 1986). Therefore, studies have demonstrated that concentrations of trace metals in benthic organisms are strongly correlated to the sediment easily leachable trace metals fractions after normalizing with Fe, organic matter, or the sulphur content of the adjacent sediments (Luoma and Bryan 1978;Langston 1980;Bourgoin et al 1991). However, in the case of A. granosa, further laboratory and field studies are needed to evaluate its bioindicator capacity particularly in the uptake, accumulation, and retention of available trace metals.…”
Section: N O N -R E S I D U a L Trace M E T A L Concentrationsmentioning
confidence: 99%
“…What exactly causes these differences is not quite well understood, but it can be hypothesized that they are related to: (i) differences in diet; (ii) differences in the form of ingested arsenic; (iii) seasonal changes, and (iv) the geographical area. Langston [15] reported a contamination of the mollusk Srobicularia plana, at the southwestern coast of UK and related the elevated As levels to contamination of the sediment. It seemed that seasonal variations, together with phytoplanktonic activity that changed the chemical form of dissolved As in the water column, influenced the accumulation of As by the mollusks greatly.…”
Section: As Concentrations In Fish and Shellfishmentioning
confidence: 99%